A new 1,2,3-triazole-indirubin hybrid suppresses tumor growth and pulmonary metastasis by mitigating the HGF/c-MET axis in hepatocellular carcinoma - Shalini V. Gowda; Na Young Kim; Kachigere B. Harsha; Darshini Gowda; Rajaghatta N. Suresh; Amudha Deivasigamani; Chakrabhavi Dhananjaya Mohan; Kam Man Hui; Gautam Sethi; Kwang Seok Ahn; Kanchugarakoppal S. Rangappa (Journal of Advanced Research)
Introduction: Hepatocellular carcinoma (HCC) is a fatal cancer that is often diagnosed at the advanced stages which limits the available therapeutic options. The interaction of HGF with c-MET (a receptor tyrosine kinase) results in the activation of c-MET which subsequently triggers the PI3K/Akt/mTOR axis. Overexpression of c-MET in HCC tissues has been demonstrated to contribute to tumor progression and metastasis. Objectives: We aimed to synthesize triazole-indirubin conjugates, examine their growth suppressor efficacy in cell-based assays, and investigate the antitumor as well as antimetastatic activity of lead cytotoxic agent in the orthotopic mice model. Methods: A series of triazole-indirubin hybrids were synthesized and cytotoxicity, apoptogenic, and antimigratory effect of the lead compound (CRI9) was evaluated using MTT assay, cell cycle analysis, annexin-V/PI assay, TUNEL assay, and wound healing assay. The effect of CRI9 on the operation of the HGF/c-MET/PI3K/Akt/mTOR axis was examined using western blotting and transfection experiments. Acute toxicity, antitumor, and antimetastatic activity of CRI9 were examined in NCr nude mice. The expression of c-MET/PI3K/Akt/mTOR, CD31, and Ki-67 was examined using immunohistochemistry and western blotting. Results: Among the new compounds, CRI9 consistently displayed potent cytotoxicity against HGF-induced HCC cells. CRI9 induced apoptosis as evidenced by increased sub G1 cells, annexin-V+/PI+ cells, TUNEL+ cells, and cleavage of procaspase-3 and PARP. CRI9 inhibited HGF-induced phosphorylation of c-METY1234/1235 and subsequently suppressed the PI3K/Akt/mTOR axis. Also, depletion of c-MET or inhibition of c-MET by CRI9 resulted in suppression of the PI3K/Akt/mTOR axis. CRI9 showed no toxic effects in NCr nude mice and displayed a potent antitumor and antimetastatic effect in the orthotopic HCC mice model. CRI9 also reduced the levels of phospho-c-MET, CD31, and Ki-67 and suppressed the activation of the PI3K/Akt/mTOR axis in tumor tissues. Conclusion: CRI9 has been identified as a new inhibitor of the c-MET/PI3K/Akt/mTOR axis in HCC preclinical models.